Paleotectonic and paleogeographic history of the Arctic region - Blakey, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2021)
Paleogeographic maps represent the ultimate synthesis of complex and extensive geologic data and express pictorially the hypothetical landscape of some region during a given time-slice of deep geologic time. Such maps, presented as paired paleogeographic and paleotectonic reconstructions, have been developed to portray the geologic history of the greater Arctic region over the past 400 million years. Collectively they depict four major episodes in the development of the Arctic region. The first episode witnessed early and middle Paleozoic terrane assembly and accretion during the Caledonian and Ellesmerian orogenies, which brought together many pieces of the Arctic collage along the northern margin of Laurussia. During the second phase, the assembly of Pangea in the late Paleozoic joined Siberia to Laurussia, an entity that became Laurasia during the subsequent break-up of Pangea. Then, Mesozoic subduction and terrane accretion constructed the Cordilleran margin and opened the Canada Basin. Finally, Cenozoic North Atlantic sea-floor spreading fully opened the Arctic Ocean.